PENGARUH FINGER PAINTING TERHADAP KEMAMPUAN MOTORIK HALUS ANAK USIA 4–5 TAHUN DI PAUD AFIFAH MARPOYAN DAMAI PEKANBARU - Yanti, Fitria; Chairilsyah, Daviq; Hukmi, Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims 1) To determine the fine motor skills of children aged 4-5 years in Paud Afifah Marpoyan Damai Pekanbaru before the application of finger painting activities. 2) To know the fine motor skills of children aged 4-5 years in Paud Afifah Marpoyan Damai Pekanbaru after the application of finger painting activities. 3) To determine how much influence the application of finger painting activities against the fine motor skills of children aged 4-5 years in Paud Afifah Marpoyan Damai Pekanbaru. This type of research used in this research is the experimental approach of a study that sought influence of certain variables on other variables in strictly controlled conditions. The study sample that Paud Afifah Marpoyan Damai Pekanbaru 20 children, 10 boys and 10 girls. Collecting data using observation and documentation. Based on the survey results revealed that 1) the fine motor skills of children aged 4-5 years in Paud Afifah Marpoyan Damai Pekanbaru before treatment is given in the form of finger painting activity is low. 2) fine motor skills of children aged 4-5 years in Paud Afifah Marpoyan Damai Pekanbaru after treatment is given in the form of finger painting activity has increased and is high. 3) The finger painting have a significant impact on fine motor skills of children aged 4-5 years in Paud Afifah Marpoyan Damai Pekanbaru. It can be seen that there are differences in the form of increased fine motor skills children before and after treatment. Finger painting activities have the effect of 41.33% of the fine motor skills of children aged 4-5 years in Paud Afifah Marpoyan Damai Pekanbaru.Keywords: Finger Painting, Fine Motor